Creating the Ancient Rhetorical Tradition - Viidebaum, Laura (Humanities, 2021)
Examines how different aspects of rhetorical theory gradually came to be associated from Plato's Phaedrus onwards with the two outstanding writers in fourth-century BCE Athens, Lysias and Isocrates, and how in first-century BCE Rome Dionysius of Halicarnassus proposed to unite them to create the foundation for the ancient rhetorical tradition.